Assessment of lung function in asthma and COPD using hyperpolarized 129Xe chemical shift saturation recovery spectroscopy and dissolved‐phase MRI. (22nd August 2014) - Qing, Kun; Mugler, John P.; Altes, Talissa A.; Jiang, Yun; Mata, Jaime F.; Miller, G. Wilson; Ruset, Iulian C.; Hersman, F. William; Ruppert, Kai; Rizi, Rahim R.
<x xml:space="preserve">Abstract</x> Magnetic‐resonance spectroscopy and imaging using hyperpolarized xenon‐129 show great potential for evaluation of the most important function of the human lung ‐‐ gas exchange. In particular, chemical shift saturation recovery (CSSR) xenon‐129 spectroscopy provides important physiological information for the lung as a whole by characterizing the dynamic process of gas exchange, while dissolved‐phase (DP) xenon‐129 imaging captures the time‐averaged regional distribution of gas uptake by lung tissue and blood. Herein, we present recent advances in assessing lung function using CSSR spectroscopy and DP imaging in a total of 45 subjects (23 healthy, 13 chronic obstructive pulmonary disease (COPD) and 9 asthma). From CSSR acquisitions, the COPD subjects showed red blood cell to tissue–plasma (RBC‐to‐TP) ratios below the average for the healthy subjects (p < 0.001), but significantly higher septal wall thicknesses as compared with the healthy subjects (p < 0.005); the RBC‐to‐TP ratios for the asthmatic subjects fell outside two standard deviations (either higher or lower) from the mean of the healthy subjects, although there was no statistically significant difference for the average ratio of the study group as a whole. Similarly, from the 3D DP imaging acquisitions, we found that all the ratios (TP to gas phase (GP), RBC to GP, RBC to TP) measured in the COPD subjects were lower than those from the healthy subjects (p < 0.05 for all ratios), while these ratios in the asthmatic subjects differed considerably between subjects. Despite having been performed at different lung inflation levels, the RBC‐to‐TP ratios measured by CSSR and 3D DP imaging were fairly consistent with each other, with a mean difference of 0.037 (ratios from 3D DP imaging larger). In ten subjects the RBC‐to‐GP ratios obtained from the 3D DP imaging acquisitions were also highly correlated with their diffusing capacity of the lung for carbon monoxide per unit alveolar volume ratios measured by pulmonary function testing (R = 0.91). Copyright © 2014 John Wiley & Sons, Ltd.